Electroencephalographic (EEG) Photoparoxysmal Responses Under 5 Years of Age: Diagnostic Implications and Peculiarities. (November 2015) - Binelli, Simona; Ragona, Francesca; Canafoglia, Laura; Freri, Elena; Saletti, Veronica; Casazza, Marina; Gilioli, Isabella; D'Arrigo, Stefano; Visani, Elisa; Panzica, Ferruccio; Granata, Tiziana; Riva, Daria; et al.
Electroencephalographic (EEG) photoparoxysmal response has been little investigated in very young patients. We studied 5055 patients aged less than 5 years with no acquired brain damage, who underwent EEG recording. We determined the prevalence and significance of photoparoxysmal response induced by 1 to 20 Hz photic stimulation. Fifty-three showed photoparoxysmal response and were diagnosed as having Dravet syndrome (11), epileptic encephalopathy with myoclonic seizures (8), neurodegenerative disorders (8), benign idiopathic epilepsies (9), and static disorders with a known or suspected genetic origin (17). Photoparoxysmal response occurred in response to 1 to 5 Hz trains in 41.5% subjects. In most patients with epileptic encephalopathies, photoparoxysmal response was a transient finding: in 53.2%, it failed to be replicated in the recordings performed more than 6 months after initial evaluation. Photoparoxysmal response is rare in patients aged less than 5 years and has some peculiarities such as occurrence with low-frequency stimuli. Its distribution in specific conditions indicates that photoparoxysmal response may be useful in diagnostic workup.